The Identification of Optimal Frequency for Ultrasonic Transducers in Concrete-Defect Detection using COMSOL® Simulator - Farah Aina Jamal Mohamad; Anita Ahmad; Ruzairi Abdul Rahim; Sallehuddin Ibrahim; Juliza Jamaludin; Noorhazirah Sunar (Penerbit UTM Press, 2026)
Indexed by MyCite